Targeting Differential Roles of Tumor Necrosis Factor Receptors as a Therapeutic Strategy for Glaucoma - Lambuk, Lidawani; Ahmad, Suhana; Sadikan, Muhammad Zulfiqah; Nordin, Nor Asyikin; Kadir, Ramlah; Nasir, Nurul Alimah Abdul; Chen, Xin; Boer, Jennifer; Plebanski, Magdalena; Mohamud, Rohimah (Frontiers in Immunology, 2022)
Glaucoma is an irreversible sight-threatening disorder primarily due to elevated intraocular pressure (IOP), leading to retinal ganglion cell (RGC) death by apoptosis with subsequent loss of optic nerve fibers. A considerable amount of empirical evidence has shown the significant association between tumor necrosis factor cytokine (TNF; TNFα) and glaucoma; however, the exact role of TNF in glaucoma progression remains unclear. Total inhibition of TNF against its receptors can cause side effects, although this is not the case when using selective inhibitors. In addition, TNF exerts its antithetic roles via stimulation of two receptors, TNF receptor I (TNFR1) and TNF receptor II (TNFR2). The pro-inflammatory responses and proapoptotic signaling pathways predominantly mediated through TNFR1, while neuroprotective and anti-apoptotic signals induced by TNFR2. In this review, we attempt to discuss the involvement of TNF receptors (TNFRs) and their signaling pathway in ocular tissues with focus on RGC and glial cells in glaucoma. This review also outlines the potential application TNFRs agonist and/or antagonists as neuroprotective strategy from a therapeutic standpoint. Taken together, a better understanding of the function of TNFRs may lead to the development of a treatment for glaucoma.